Pidgin Language at Present: The Alternative Language for Nigerian Contemporary Performing Artists - Rukaye, OHWONOHWO Titus; Ebele, CHIEDU Rosemary (International Journal of Linguistics, Literature and Translation, 2021)
Pidgin language (PL) is cardinal o many Nigerians especially in the South-South region, where the language is mostly used. The pidgin language is mostly employed to solve the issues of language difficulties in terms of usage. This is because of the enormous population of illiterates in Nigeria. The pidgin language is for everybody: the educated, uneducated, rich, poor, etc. The way it is used in Nigeria and elsewhere does not require one going to school to study it before one can actually speak it. It is a fast-growing language in Nigeria. New lexical items are brought into the province of the language daily especially by Nigerian musicians from the Niger-Delta and Lagos areas. The pidgin language that has been frowned at decades ago is now a contemporary communicative instrument used by different people and for different purposes. This paper, therefore, seeks to demonstrate that pidgin language plays a prevailing role than English Language in Nigeria these days. The paper goes further to state that in the absence of the pidgin language, disseminating messages through songs will not get to the actual target.